2016
DOI: 10.1007/s12257-015-0384-6
|View full text |Cite
|
Sign up to set email alerts
|

A rapidly new-typed detection of norovirus based on F0F1-ATPase molecular motor biosensor

Abstract: In order to adapt port rapid detection of food borne norovirus, presently we developed a new typed detection method based on F 0 F 1 -ATPase molecular motor biosensor. A specific probe was encompassed the conservative region of norovirus and F 0 F 1 -ATPase within chromatophore was constructed as a molecular motor biosensor through the "ε-subunit antibody-streptomycinbiotin-probe" system. Norovirus was captured based on probe-RNA specific binding. Our results demonstrated that the Limit of Quantification (LOQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The F0F1-ATPase molecular motor biosensor was applied to detect NV RNA with a "ε-subunit antibody-streptomycinbiotin-probe" system. The fluorescence intensity change compared to the control showed that the virus was successfully captured and conjugated to the probe [142]. Due to much lower background noise, chemiluminescence was described to be more sensitive than UV-vis absorbance and fluorescence [143].…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The F0F1-ATPase molecular motor biosensor was applied to detect NV RNA with a "ε-subunit antibody-streptomycinbiotin-probe" system. The fluorescence intensity change compared to the control showed that the virus was successfully captured and conjugated to the probe [142]. Due to much lower background noise, chemiluminescence was described to be more sensitive than UV-vis absorbance and fluorescence [143].…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
“…This assay could achieve a LOD of 16 fM and a single-molecule sensitivity, since individual vesicles could be visualized by TIRF microscopy [140]. In another study conducted by Connelly et al [141], a fluorescence based microfluidic biosensor was shown to be able to detect FCV with a LOD of 1.6 × 10 5 PFU/mL within 2.5 h. Another fluorescence based biosensor developed by Zhao et al [142] had been shown to be able to detect NV RNA with a limit of quantification of 0.005 ng/mL within 1 h. The F0F1-ATPase molecular motor biosensor was applied to detect NV RNA with a "ε-subunit antibody-streptomycin-biotin-probe" system. The fluorescence intensity change compared to the control showed that the virus was successfully captured and conjugated to the probe [142].…”
Section: Other Optical Biosensor Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A molecular motor F 0 F 1 -ATPase biosensor is designed to detect foodborne noroviruses based on probe-RNA specific binding 123 . A specific probe is designed to encompass a conservative region of noroviruses; and F 0 F 1 -ATPase in chromatophore is constructed as a molecular motor to drive the biosensor in noroviruses capturing.…”
Section: Other Advanced Technologies In Poc Of Foodborne Virusesmentioning
confidence: 99%